Development of Islamic Education Curriculum: Conceptual Study of Thematic Qur'anic Interpretation Perspectives - Muhammad Ghafar (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2021)
Abstract This article describes the curriculum in Islamic education with the results of the analysis of the study, which concludes first, the content of the curriculum is oriented to